1992
DOI: 10.1017/s0263593300007987
|View full text |Cite
|
Sign up to set email alerts
|

The role of magma sources, oxidation states and fractionation in determining the granite metallogeny of eastern Australia

Abstract: The ore-element associations of granite-related ore deposits in the eastern Australian Palaeozoic fold belts can be related to the inferred relative oxidation state, halogen content and degree of fractional crystallisation within the associated granite suites. Sn mineralisation is associated with both S- and I-type granites that are reduced and have undergone fractional crystallisation. Cu and Au are associated with magnetite- and/or sphene-bearing, oxidised, intermediate I-type suites. Mo is associated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…The regional petrographic and compositional similarities among granites in the Lachlan Fold Belt (LFB) that define nine distinctive petrographic provinces were correlated by with basement terranes, the boundaries between which generally correlate poorly with any tectonostratigraphic boundaries based on geological features exposed at the surface. The distribution of those granite basement terranes was subsequently shown by Blevin and Chappell (1992) to be strongly correlated with the distribution of granite-related mineralisation within the LFB, suggesting that strong genetic links exist between granite source compositions and the ore element ratios of associated mineralisation. If magmatic compositions and processes determine ore element ratios in granite-related mineralisation, then the distribution of those source regions will be one of several important controls on the distribution of such mineralisation.…”
mentioning
confidence: 99%
“…The regional petrographic and compositional similarities among granites in the Lachlan Fold Belt (LFB) that define nine distinctive petrographic provinces were correlated by with basement terranes, the boundaries between which generally correlate poorly with any tectonostratigraphic boundaries based on geological features exposed at the surface. The distribution of those granite basement terranes was subsequently shown by Blevin and Chappell (1992) to be strongly correlated with the distribution of granite-related mineralisation within the LFB, suggesting that strong genetic links exist between granite source compositions and the ore element ratios of associated mineralisation. If magmatic compositions and processes determine ore element ratios in granite-related mineralisation, then the distribution of those source regions will be one of several important controls on the distribution of such mineralisation.…”
mentioning
confidence: 99%
“…The oxygen fugacity of a granitic magma can reflect the redox state of the source region, as well as influence the processes of metal enrichment in the magma (Ishihara 1981;Candela 1989;Carmichael 1991;Blevin & Chappell 1992). Several features Plot of E Nd versus initial Sr ratio for Tombstone, Mayo and Tungsten plutonic suites using data compiled from Godwin et d. (1980), Kuran et d. (1982), Gareau (1986), Abercrombie (1990), Lang (2000) and Farmer et d. (2000).…”
Section: Redox Statementioning
confidence: 99%
“…Ishihara 1977Ishihara , 1981Blevin & Chappell 1992). Ishihara (1977Ishihara ( , 1981 indicated that the compatibility and partitioning behaviour of metals is strongly influenced by the oxidation state of a magma, which can be estimated based on the dominance of either magnetite or ilmenite.…”
Section: Relationships Between the Redox State Of Magmas And Metallogenymentioning
confidence: 99%
See 2 more Smart Citations